ANALISIS PENGADAAN OBAT PROGRAM RUJUK BALIK DAN PROLANIS DI APOTEK SANA FARMA KOTA SEMARANG DALAM PRESPEKTIF INPUT - Murni Murni; Septo Pawelas Arso; Rani Tyas Budiyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Sosial and Health Insurance Administration Organization in choosing network health facilities are used several criteria include the human resources, infrastructure, service scope and commitment, this is a demand for health facilities in collaboration with BPJS Kesehatan to improve the quality of existing resources. The pharmacy as a network health facility serves as the person in charge of ensuring the availability of medicines for the Referral and the Chronic Disease Management Program. So to guaranted the availability of drugs and it was not empty, the government was provided e-purchasing access to the pharmacy collaboration with Health Insurance Administration Organization in the procurement of drugs and it is expected that the pharmacy can increase the quality of the resources it has. The purpose of the study was to analyze the procurement of drugs related to the Referral Program and the Chronic Disease Management Program at the Sana Farma Pharmacy in the input perspective (labor, budget, prosedure, facilities). This research is qualitative research with descriptive analytic approach. Data collection was conducted using an indepth interview method, selected based on purposive technique. The research subject was the pharmacy staff (Procurement Staff, Pharmacists, Finance Staff, Billing and Entry Staff, and Pharmacist Assistant) while the triangulation informants were the Pharmacy Manager and BPJS Health Quality Assurance Chief. The factors studied were labor, budget, prosedure, facilities. The results of the study there is a mismatch between what is implement by Sana Farma Pharmacy and applicable regulations on labor factors, there was no training, the budget have delay in disbursement, inadequate facilities, the SOPs for the procurement of Referral and the Chronic Disease Management Program drugs were not available. The results of this study suggest improving infrastructure to support the procurement of Referral and the Chronic Disease Management Program drugs to be effective and efficient procurement.